Flexible Electronics: An Epidermal Stimulation and Sensing Platform for Sensorimotor Prosthetic Control, Management of Lower Back Exertion, and Electrical Muscle Activation (Adv. Mater. 22/2016). Issue 22 (6th June 2016) - Xu, Baoxing; Akhtar, Aadeel; Liu, Yuhao; Chen, Hang; Yeo, Woon‐Hong; Park, Sung II; Boyce, Brandon; Kim, Hyunjin; Yu, Jiwoo; Lai, Hsin‐Yen; Jung, Sungyoung; Zhou, Yuhao; et al.
Abstract : The design of an ultrathin, conformal electronic device that integrates electrotactile stimulation with electromyography, temperature, and strain sensing in a single, simple platform is reported by J. A. Rogers and co‐workers on page 4462. Demonstrated application possibilities include prosthetic control with sensory feedback, monitors, and stimulation signals related to lower back exertion, and electrical muscle stimulation with feedback control.